Don't Look Down: The Limits of Meroscopic Measurement - Swenson, Sue (Frontiers in Rehabilitation Sciences, 2022)
The essay examines some problems and opportunities of outcomes measures from a philosophical, political, and human rights perspective. Two suggestions for further effort are included: establish a person-centered outcomes research entity to help make outcomes measures more useful in decision-making and use a human rights framework to understand the impact toward which projects and programs aim.